Progress on laser induced fluorescence in a collisional environment: the case of OH molecules in ns pulsed discharges. (28th February 2019) - Dilecce, G; Martini, L M; Ceppelli, M; Scotoni, M; Tosi, P
Abstract: A nanosecond discharge imposes severe challenges to the application of laser induced fluorescence (LIF), due to the nature of its variable and hot collisional environment. In this paper, we review these difficulties, the current knowledge on collision processes and the concept of collision energy transfer LIF (CET-LIF). The application of CET-LIF to nanosecond discharges for CO2 dissociation shows results that make this challenge worth pursuing.